Advanced diagnosis of vibriosis among some marine fishes in lake Temsah, Egypt - EISSA, IAM; ABOU-ELGHEIT, S. N.; DESSUKI, A. A.; HASSANIN, A.A.I.; MOSTAFA, L. T. (Journal of the Hellenic Veterinary Medical Society, 2019)
Vibriosis is a serious disease affecting marine water fishes. The present study was applied on 320 marine fishes of four equal different species (Sparus auratus, Mugil cephalus, Mugil seheli and Tilapia zillii) each 80. Fishes were collected seasonally and randomly from Lake Temsah in Ismailia governorate from September 2015 to August 2016. The signs and lesions of severe septicemia, hemorrhages and ulcerations were observed among the examined fishes. Isolated bacteria were observed as yellow and green pigmented colonies on TCBS media, and as creamy colored colonies on TSA media with 2.5% NaCl concentration. The causative agent was identified as vibrio sp. Concerning gene expression, most isolates were molecularly identified using the pvsA gene primers giving a product size of 338-bp size and 348-bp for V. alginolyticus and V. parahemolyticus respectively. The highest prevalence of vibriosis was recorded in T. zillii (63.75%), M.seheli (37.5%) then M.cephalus and Sparus auratus (28.75%) while the total prevalence was (39.69%). The highest seasonal prevalence was recorded in summer (81.25%) followed by spring (35%) then autumn (23.75%) and winter (18.75%). The highest prevalence of organ specifity was in liver, kidneys then spleen and gills. The histopathological studies showed activation of melanomacrophage centers, degeneration, necrosis and congestion in liver, kidney, spleen, and gills.